Análisis de la estructura narrativa empleada por el gobierno peruano en las campañas de comunicación sobre prevención del COVID-19 - Chávez Hinojosa, Luis Alvaro (2022)
The covid-19 pandemic has meant an unprecedented health and economic crisis for Peru, for which the government was obliged to develop different communication campaigns to encourage all the preventive measures on the Peruvian society. This research analyzed the narrative structure of two communication campaigns issued by the Peruvian government during the pandemic stage through content analysis and interviews with the target audience. It was concluded that in the narrative of these campaigns, messages with a fearful, threatening and informative approach were prioritized, which generated a low level of identification and emotion in the audience.